Pengaruh Variasi pH Saliva terhadap Perlekatan Streptococcus mutans pada Resin Komposit Nanofil - Rahma Syarafina Maharani; Widowati Siswomiharjdo; Siti Sunarintyas (Jurnal Material Kedokteran Gigi, 2017)
Nanofilled composite resin restorations are in contact with saliva.Salivary pH affect the hydrolysis process and produce a surface roughness.S.mutansadhesion occur in a rough area of the oral cavity.The aim was to determine the effect of variations in salivary pHonS.mutansadhesion to nanofilled composite resin.Nanofilled composite resin(Filtex Z350XT-3M ESPE)5mm diameter and 2mm thick(N=12)were divided into three groups(n=4)and immersed in 5ml artificial saliva pH 3.5, pH 7, pH 8, incubated 14 days,37°C. Samples were soaked into saliva 1 hour,37 C. Samples were put into bacterial suspension 24 hours,37°C, diluted to 10.0.1ml of the final dilution were cultured on BHI agar, incubated 48 hours,37°C. S.mutans colonies were determined using Colony Counter(CFU/ml). Data were analyzed with One-Way ANOVA test(a=0.05) and LSD0.05. The test showed there is influence ofthe variations in salivary pHonS.mutans adhesionto nanofilled composite resin(p<0.05). Based on LSD0.05 test, there are significant differences between the pH 3.5 group and the pH 7; pH 8 groups, butnot between the pH 7group and the pH 8 group. Variations in salivary pH affectedS.mutansadhesion to nanofilled composite resin.The acidic pH of saliva increased the S.mutansadhesion on nanofilled composite resin compared with the neutral or alkaline.